2015
DOI: 10.1002/soej.12101
|View full text |Cite
|
Sign up to set email alerts
|

Does health insurance decrease health expenditure risk in developing countries? The case of China

Abstract: This article studies the impact of health insurance on individual out-of-pocket health expenditures in China. Using China Health and Nutrition Survey data between 1991 and 2006, we apply twopart and sample selection models to address issues caused by censored data and selection on unobservables. We find that, although the probability of accessing health care increases with the availability of health insurance, the level of out-of-pocket health expenditure decreases. Our results from a selection model with inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
29
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 25 publications
7
29
3
Order By: Relevance
“…The results of this study were in agreement with those of Jung and Liu Streeter 34 and some other similar authors, 35,36 who reported that income had a positive effect on the cost of OOP payment.…”
Section: Discussionsupporting
confidence: 93%
“…The results of this study were in agreement with those of Jung and Liu Streeter 34 and some other similar authors, 35,36 who reported that income had a positive effect on the cost of OOP payment.…”
Section: Discussionsupporting
confidence: 93%
“…While column (3) shows that health insurance increases the probability of using inpatient healthcare, column (4) Jung and Streeter, 2015). Besides the differences in data and methodologies used, the time scopes of the studies could also be a reason for these different findings.…”
Section: Overall Effectmentioning
confidence: 99%
“…This is likely due to healthcare users switching to more costly and higher-level providers, as well as higher utilization rates among the insured (Jung and Streeter, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More attention should be paid to the PHI market and purchasing behavior in China. Systematic research on health insurance has shown that more attention was paid to SBMI than to PHI-for example, the impact of the NCMS on the reduction of out-of-pocket medical expenditures, thereby improving financial protection [13][14][15], and the role played by other schemes such as UEBMI in containing health expenditures [16]; the role of SBMI in lowering catastrophic health expenditures and increasing outpatient expenditure reimbursement [1][2][3]17,18]. Studies on PHI have mainly focused on the way in which the expansion of SBMI has affected the development of PHI [19].…”
Section: Introductionmentioning
confidence: 99%